Invasive mosquito vectors in Europe: from bioecology to surveillance and management - Giunti, Giulia; Becker, Norbert; Benelli, Giovanni (Acta tropica, 2023)
Invasive mosquitoes (Diptera: Culicidae) play a key role in the spread of a number of mosquito-borne diseases worldwide. Anthropogenic changes play a significant role in affecting their distribution. Invasive mosquitoes usually take advantage from biotic homogenization and biodiversity reduction, therefore expanding in their distribution range and abundance. In Europe, climate warming and increasing urbanization are boosting the spread of several mosquito species of high public health importance. The present article contains a literature review focused on the biology and ecology of Aedes albopictus, Ae. aegypti, Ae. japonicus japonicus, Ae. koreicus, Ae. atropalpus and Ae. triseriatus, outlining their distribution and public health relevance in Europe. Bioecology in-sights were tightly connected with vector surveillance and control programs targeting these species. In the final section, a research agenda aiming for the effective and sustainable monitoring and control of invasive mosquitoes in the framework of Integrated Vector Management and One Health is presented. The WHO Vector Control Advisory Group recommends priority should be given to vector control tools with proven epidemiological impact.
Gesehen am 28.03.2023